Prevalence of dyspnea and/or chest pain persistence at mid-term after COVID-19 infection: a systematic review and meta-analysis. (14th October 2021) - Mustafic, H; Cekovic, D; Yordanov, Y; Dinh, A; Helft, G; Jourdain, P
Abstract: Introduction: COVID-19 is a recent infection that affects the whole world. Symptoms such as dyspnea and/or chest pain may persist in some people after the acute infection phase. However, the extent of this phenomenon is not yet well known. Purpose: To determine the prevalence of dyspnea and/or chest pain at least at one month after COVID-19 infection diagnosis. Methods: EMBASE, Ovid MEDLINE in-process and other nonindexed citations, and Ovid MEDLINE (between 1948 and January 15, 2021), and EBM Reviews-Cochrane Central Register of Controlled Trials and EBM Reviews-Cochrane Database of Systematic Reviews (between 2005 and January 15, 2021) were searched for a combination of keywords related to the type of exposure (COVID-19 infection) and to the type of outcomes (dyspnea persistence and/or chest pain persistence at least one month after COVID-19 infection diagnosis). Two independent reviewers selected studies of any design and in any language, using original data. Descriptive and quantitative information was extracted from each selected study and study quality was also assessed. We estimated prevalence in percentage and 95% Cis for each outcome, using a random-effects model. Statistical heterogeneity across the studies was calculated by the I 2 statistic to quantify inconsistencies between studies. To assess the potential for publication bias, we visually inspected funnel plots and added the Egger's regression test p-value for funnel symmetry. Results: After an exhaustive screening of 1287 citations in title and abstract, 31 studies were reviewed from entire article and 10 studies with 2004 patients were finally selected for meta-analysis. Interrater agreements were very high (0.91 and 1 respectively for the two selection steps). The pooled dyspnea persistence prevalence from 10 studies was of 39%; 95% Ci [29%-49%], p<0.01, I 2 =91%, Egger's regression test p=0.19. The pooled chest pain persistence prevalence from 6 studies was of 18%; 95% Ci [11%-24%], p<0.01, I 2 =89%, Egger's regression test p=0.12). Conclusion: Dyspnea and/or chest pain persistence prevalences after COVID-19 infection diagnosis are unexpectedly high, at least at one month. We have to take into account high heterogeneity due to subjects characteristics, various COVID-19 infection severities and study methodologies but there were no statistical argument for a publication bias. Nevertheless, this phenomenon requires more research to determine the long-term prevalence of these symptoms persistence and the mechanisms involved. FUNDunding Acknowledgement: Type of funding sources: None.